Response of bacterial community composition and co-occurrence network to straw and straw biochar incorporation - Du, Mingcheng; Zhang, Jianyun; Wang, Guoqing; Liu, Cuishan; Wang, Zhenlong (Frontiers in Microbiology, 2022)
Microorganisms play a crucial role in the incorporation of straw and straw biochar into the soil. However, it remains unclear how their addition affects the soil bacterial community and its interactions in lime concretion black soil (LCBS). We designed four treatments (straw biochar with fertilizer, BF; straw, S; fertilizer, F; and straw with fertilizer, SF) in a field experiment to explore the effects of different depths and growth stages on bacterial community composition, structure and co-occurrence network patterns. The results showed that soil PH, soil organic matter and total nitrogen significantly affected the seasonality and stratification of soil bacterial community in different treatments. The composition and diversity of bacterial communities were significantly affected by growth period and treatment rather than soil depth. Specifically, the bacterial community diversity increased significantly with crop growth at 0–20 cm, decreased the relative abundance of Actinobacteria, and increased the relative abundance of Proteobacteria and Acidobacteria. SF and BF treatments decreased bacterial community diversity, but the number of edges network pattern was increased by 92.5%, 40%, and 60% in the BF, S, and SF treatments at maturity stage compared with F treatment, respectively. More positive links between bacterial communities were also observed in the BF, S, and SF treatments. This indicated that straw and straw biochar incorporation enhanced the complexity and stability of soil bacterial network. Moreover, the positive effect of straw biochar on the bacterial network pattern increased with time, while the effect of straw weakened. Notably, we found that rare species inside keystone taxa (Gemmatimonadetes and Nitrospirae) play an indispensable role in maintaining bacterial network construction in LCBS. In conclusion, the incorporation of straw and straw biochar helps to enhance the synergistic effect of soil bacterial community and promote material circulation, and the enhancement effect of straw biochar is more durable.